Analisis Implementasi Kebijakan Insentif Pajak Penghasilan Pasal 25 Masa Pandemi Covid-19 Dalam Rangka Meningkatkan Penerimaan Negara Pada Kantor Pelayanan Pajak Pratama Jakarta Kebon Jeruk Satu Tahun 2020 - Clara Clarita; Chairil Anwar Pohan (Jurnal Ilmu Administrasi Publik, 2021)
The Covid-19 outbreak in Indonesia began in March 2020 and this condition greatly affects economic stability and community productivity, especially as business actors. This makes the government make efforts to regulate taxes by issuing tax incentive policies, one of which contains a reduction in the installment of article 25 Income Tax payments. This research aims to analyze the policy implementation of the article 25 income tax incentive in increasing state revenues in 2020 during the COVID-19 pandemic at KPP Pratama Jakarta Kebon Jeruk Satu. The research method used is descriptive qualitative and the data collection techniques are interviews, documentation studies and triangulation of sources. The results of this research indicate that the policy implementation of the Article 25 Income Tax incentive in 2020 is not yet optimal because the realization of Article 25 corporate income tax revenue has not yet been optimally achieved in 2020 at 94.95%. When compared to 2019, the nominal target and realization of article 25 income tax of 2020 has decreased. In this case, the weakness of the incentive is that not all corporate taxpayers can take advantage of it. However, by maintaining tax or state revenues at KPP Pratama Jakarta Kebon Jeruk Satu and economic stability, it can increase the purchasing power of the public, investors and maintain cash flow of business actors. On the other hand, it is expected that tax revenues from other tax sectors can help increase tax revenues at KPP Pratama Jakarta Kebon Jeruk Satu or state tax revenues. KPP Pratama Jakarta Kebon Jeruk must also carry out socialization and counseling maximally.